Physical activity promotion at the local government level among the local community - Sobczyk, Karolina; Grajek, Mateusz; Rozmiarek, Mateusz; Sas-Nowosielski, Krzysztof (Journal of Education, Health and Sport, 2022)
Physical inactivity is a major public health issue. For the prevention and management of noncommunicable diseases (NCDs), such as cardiovascular disease, type-2 diabetes, and a number of malignancies, regular physical activity is a critical protective factor. Along with helping to maintain a healthy weight and overall wellbeing, physical activity has positive effects on mental health, including the avoidance of cognitive decline and the symptoms of despair and anxiety. Local governments all across the world have responded to this problem by launching population-level projects that give locals access to exercise opportunities. Local governments, through the implementation of their own tasks of health promotion and protection, carry out public health tasks as defined by the Law of 11 September 2015 on Public Health. These tasks include activities in the area of physical activity. The aim of the article was to show the role of local government in promoting physical activity among the local community. The article discusses such issues as WHO recommendations for physical activity as well as activities undertaken by local governments in the area of health promotion in the form of health policy programs and activities carried out in cooperation with NGOs.